Caught Between Delay and Distress: Examining the Role of Self-Compassion in the Relationship between Procrastination and Academic Stress among Migrant Students - Ardelia Yudhistira, Izza; Sandjaja, Meilani (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
Higher education in Indonesia provides opportunities for personal and academic development, yet migrant students often face complex challenges, including adapting to new social and academic environments, managing independent living, and meeting high academic demands, which can lead to procrastination and increased academic stress. This study examined the relationship between academic procrastination and academic stress among migrant university students, with self-compassion as a mediating variable. A quantitative correlational design with mediation analysis was employed, involving 140 migrant students who completed online self-report questionnaires measuring academic procrastination, academic stress, and self-compassion. Mediation analysis using JASP 18.3 and bootstrapping showed that academic procrastination had a significant positive effect on academic stress (estimate = 0.338, p < .001), while self-compassion partially mediated this relationship, reducing the stress associated with procrastination (indirect effect = 0.084, p = 0.005). The total effect of procrastination on stress was also significant (estimate = 0.442, p < .001). These results indicate that self-compassion acts as a protective factor, helping migrant students cope with the psychological burden of procrastination. Interventions aimed at fostering self-compassion may therefore enhance emotional well-being, academic adjustment, and resilience, supporting students in managing academic challenges and promoting success in higher education contexts.Pendidikan tinggi di Indonesia memberikan peluang untuk pengembangan pribadi dan akademik. Namun, mahasiswa migran sering menghadapi tantangan yang kompleks, termasuk beradaptasi dengan lingkungan sosial dan akademik yang baru, mengelola kehidupan mandiri, serta memenuhi tuntutan akademik yang tinggi, yang dapat menyebabkan prokrastinasi dan meningkatnya stres akademik. Penelitian ini mengkaji hubungan antara prokrastinasi akademik dan stres akademik pada mahasiswa migran, dengan self-compassion sebagai variabel mediasi. Desain penelitian yang digunakan adalah kuantitatif korelasional dengan analisis mediasi, melibatkan 140 mahasiswa migran yang mengisi kuesioner daring berbasis self-report untuk mengukur prokrastinasi akademik, stres akademik, dan self-compassion. Analisis mediasi menggunakan JASP 18.3 dan teknik bootstrapping menunjukkan bahwa prokrastinasi akademik memiliki pengaruh positif yang signifikan terhadap stres akademik (estimate = 0,338, p < 0,001), sementara self-compassion memediasi secara parsial hubungan tersebut dengan menurunkan tingkat stres yang terkait dengan prokrastinasi (indirect effect = 0,084, p = 0,005). Pengaruh total prokrastinasi terhadap stres juga signifikan (estimate = 0,442, p < 0,001). Hasil ini menunjukkan bahwa self-compassion berperan sebagai faktor protektif yang membantu mahasiswa migran mengatasi beban psikologis akibat prokrastinasi. Oleh karena itu, intervensi yang bertujuan untuk meningkatkan self-compassion dapat memperkuat kesejahteraan emosional, penyesuaian akademik, dan resiliensi, sehingga mendukung mahasiswa dalam menghadapi tantangan akademik dan mencapai keberhasilan di pendidikan tinggi.